Children’s rights with disabilities and alternative care between universal and regional (Council of Europe) standards of protection - Wedel Domaradzka, Agnieszka (European Integration Studies, 2023)
The study deals with issues relating to alternative institutional care to which children, particularly children with disabilities, are subjected. In the case of these children, there is often a multiple 'sensitisation' situation - not only are they minors, but they are deprived of parental care and have intellectual or physical disabilities. The legal regulations for children in such situations will be presented. Soft-law guidelines representing demands for adoption and implementation at the national level will also be identified and discussed. A separate analysis will be made of the jurisprudence of the European Court of Human Rights on children in institutional care and how and to what extent this jurisprudence effectively influences the level of protection. In this aspect, particular attention will be paid to the issue of the vindication of violations of law violations by victims and the possible possibilities of making legal standing more flexible.